Algorithms in a Robust Hybrid CFD-DEM Solver for Particle-Laden Flows (Communications in Computational Physics, 2018)
A robust and efficient solver coupling computational fluid dynamics (CFD)with discrete element method (DEM) is developed to simulate particle-laden flows invarious physical settings. An interpolation algorithm suitable for unstructured meshesis proposed to translate between mesh-based Eulerian fields and particle-based Lagrangianquantities. The interpolation scheme reduces the mesh-dependence of the averagingand interpolation procedures. In addition, the fluid-particle interaction termsare treated semi-implicitly in this algorithm to improve stability and to maintain accuracy.Finally, it is demonstrated that sub-stepping is desirable for fluid-particle systemswith small Stokes numbers. A momentum-conserving sub-stepping technique is introducedinto the fluid-particle coupling procedure, so that problems with a wide rangeof time scales can be solved without resorting to excessively small time steps in theCFD solver. Several numerical examples are presented to demonstrate the capabilitiesof the solver and the merits of the algorithm.